Chemical and Mineralogical Mapping of Platinum‐Group Element Ore Samples Using Laser‐Induced Breakdown Spectroscopy and Micro‐X‐Ray Fluorescence. Issue 3 (22nd June 2021) - Mohamed, Nessrine; Rifai, Kheireddine; Selmani, Samira; Constantin, Marc; Doucet, François R.; Özcan, Lütfü Ç.; Sabsabi, Mohamad; Vidal, François
Abstract : Standard techniques for geochemical and mineralogical characterisation are time‐consuming, they can involve significant sample preparation and they are prone to error. The aim of this work is to show how the emerging fast laser‐induced breakdown spectroscopy (LIBS) technique can be valuable for mineral exploration. For this purpose, the well‐established micro‐X‐ray fluorescence (µ‐XRF) technique was used to validate the LIBS data. Two ore samples from the platinum‐group elements (PGE) Lac des Îles mine (Ontario, Canada) were analysed both by LIBS and µ‐XRF. The fast mineralogical and elemental mapping provided by LIBS allowed the identification of four major silicate phases (chlorite, bytownite, actinolite, hornblende) and four minor sulfide phases (Pd‐bearing pentlandite, chalcopyrite, pyrrhotite, pyrite). Multi‐element chemical mapping and mineral characterisation using µ‐XRF corroborated the LIBS analyses for the composition, distribution and abundance of minerals in PGE ore samples. These findings demonstrate the ability of the LIBS technique to perform direct fast high‐resolution mapping of the chemical and mineralogical composition of PGE ore samples. This work highlights the advantages of LIBS for this application of being much faster and more sensitive to trace elements (e.g., Pd), as well as to low atomic number elements. Abstract : Key Points Eight mineral phases were identified automatically by laser‐induced breakdown spectroscopy (LIBS) on PGE ore samples. The main mineral phases were corroborated by μ‐XRF. Mineral maps generated by both methods are in excellent agreement (LIBS acquisition speed was 1000 spectra per second, compared with 160 spectra per second for μ‐XRF).